Investigation and optimization of methane purification method for natural gas by two-column gas chromatography: A preliminary test for doubly substituted isotopologue (13CH3D) measurements - Sun, Tiantian; Cao, Jun; Qiu, Haijun; Fu, Piaoer; Lu, Hailong; Ning, Zijie; Chen, Daohua; Deng, Yinan; Yang, Shengxiong (Frontiers in Marine Science, 2023)
In this study, optimization of the methane purification method by gas chromatography (GC) is described for the determination of methane clumped isotope compositions of natural gas. Methane was purified under the carrying of helium on the assembly line composed of a vacuum apparatus and two-column gas chromatography. Once methane was detected by the passive thermal conductivity detector (TCD) on the GC, it was collected through a silica trap immersed in liquid nitrogen. Optimum conditions of chromatographic column diameter (1/4 inch outside diameter), temperature (25 °C), and flow rate (50.8 ml min-1) have been determined. When N2/CH4 (by volume) is<8.7%, the purification experiment can be undertaken once, while a double purification experiment is required when natural gas samples have an N2/CH4 of 8.7-78.0%. The purification method yielded a purity of 98.4-98.8% with a recovery of 97.3-98.7% on purified methane samples verified by GC determination. N2 was the main source that contributed to the loss of the purity, however, the N-bearing isobaric interferences (14NH3+ and 14NH4+) in purified samples presented<1‰ intensity compared to the methane isotopologues (13CH4+ and 13CH3D+), thus we concluded that these interferences have no impact on clumped isotope determinations. The conventional δ13CVPDB and δDVSMOW values of purified methane samples were consistent with those of pure methane. A preliminary measurement of Δ13CH3D (working gas) of purified samples revealed differences of -0.27‰, which was within the internal precision of the measurement. The entire process of a single purification can be completed within two hours. Our proposed method could be used for the clumped isotope purification of natural gas with higher than ~50% methane.